# Math

posted by .

x^2 + 9y^2 = 37
x - 2y = -3
simultaneous equation by elimination

• Math -

elimination is usually done with linear equations. Using substitution,

x = 2y-3, so we have

(2y-3)^2 + 9y^2 = 37
4y^2 - 12y + 9 + 9y^2 = 37
13y^2 - 12y - 28 = 0
(y-2)(13y+14) = 0

## Similar Questions

1. ### maths

simultaneous equations x + 2y = 4 3x - 4y = 7 x=3 and y = 1/2 i need to explain how i got this answer and do not know how to do that?
2. ### maths B

i don't understand how to do simultaneous solutions of linear functions. i don't understand what elimination is and how to substitute. for eg. 4c-3d=11 3c-4d=17 is that elimination?
3. ### Physics

Two events that are simultaneous in one frame of reference will be: A) simultaneous in all frames of reference B) simultaneous in another frame that is moving in the opposite direction C) simultaneous in another frame of reference …
4. ### math simultaneous equation with surds

ive got quite far but im stuck, can you go through each stage so i can check. simultaneous equation with surds 5x-3y=41 (7root2)x+(4root2)y=82 thanks for the help
5. ### Math

x=-y+3 5x-y=-2 Solve using Elimination I already solved the equation using Substitution, Graphing, and a table I just need a little more help on Elimination. I know that in Elimination they have to be in the same form so I put it in …
6. ### Math

Solve these simultaneous linear equations using elimination method : 3a = 2b + 1 and 3b = 5a - 3
7. ### 5a-2b=14 , 2a+2b=14

Use the method of elimination to solve the following pairs of simultaneous equation 8y+4z=7 6y-8z=41
8. ### Maths

Solve Simultaneous Equetion Using Elimination Method: (A)2x - 3y= -3 and 3x - 7y= -1.
9. ### Math

Solve the simultaneous equation n/4-m/6=-1 Using elimination method
10. ### Math

Solve the simultaneous equation n/4-m/6=-1 m/5+n/2=10 Using elimination method

More Similar Questions